(untitled) (Research, Society and Development, 2025)
Hypertensive disease is a very common condition in the elderly, representing a significant challenge for health professionals, especially in the basic health care network. The present study aims to explore the difficulties related to hypertension control and its consequences in the lives of the elderly. This work is characterized as a descriptive and observational clinical investigation, adopting qualitative methods. Four nursing processes were outlined, based on the NANDA-I classification, considering the clinical case of an elderly woman, identified as A.T.M. During the interviews, relevant variables were identified, such as treatment, continuous monitoring and health education, which are essential to achieve effective blood pressure control. When hypertension is not managed properly, there is a high risk of developing serious complications, directly impacting the elderly. To minimize these risks, it is essential that there is an integrated action between the multidisciplinary team, family members and society, promoting monitoring, guidance and encouraging adherence to medical recommendations. Challenges in managing hypertension remain, requiring collaborative efforts to help maintain the disease and improve the comfort of the elderly. Therefore, multidisciplinary strategies and family support are essential to achieve better results.